Sistema de registo de identificação criminal de condenados pela prática de crimes contra a autodeterminação sexual e a liberdade sexual de menor - Prudêncio, Renato David dos Reis (2021)
The present work, under the "cover" of the law establishing the identification of convicted persons for crimes of sexual abuse of minors, intends to reflect in depth on the consequences inherent in the dissemination of the data of these agents and what justified this legislative option. We want to find out what motivations lie behind the law and what dangers and risks we face when a law with such contente is passed. Are we talking about proportional counterparts whose denied fundamental rights justify the intended end? More than a scientific study with the traditional (and indispensable) bibliographical references of a theme that has already been too much debated in the doctrine, this humble contribution consists in a thought that underlies the creation of the own law. In this sense, we proceed to a detailed (sometimes too descriptive, but necessary) analysis of the law and the aspects that we consider most relevant, so that we can form a valid and coherent thought that allows us to have sustained tools for a point of arrival. As possible, within the inevitable limitations imposed upon us. This was indeed one of the purposes that led us to systematize the work in the way we are going to present it, in which the law is initially presented and only afterwards the considerations are made, in order to present itself to the reader as uncritical. Only then do we make our critical appraisal by going within the limits imposed on us – and to address a little all the points of contact that seem relevant to us – the political motivations behind lawmaking, the context and the difficulties with which it has passed its adoption and its various amendments, its approach from the point of view of fundamental rights and the inherent axiology, as well as a brief trip to the register by other countries.